An approach to a field drainage problem by laboratory examination of selected properties of undisturbed soil cores : thesis presented at Massey University of Manawatu in part fulfilment of the requirements for the degree of Master of Agricutural Science - Baker, Christopher John (Massey University, 1964)
For many years, soil drainage investigators, from a practical view point, have had to content themselves with expert appraisal of certain direct and indirect soil and environmental characteristics in order to ascertain the cause of a particular drainage problem. In a great many instances, observations of vegetative composition, topography and general soil type, aided by aerial photography and local experience, give completely adequate information. Normally, derivation of conclusions from such observations is based on well established principles, and the recognition of general broad classes of the cause of mal-drainage conditions. Such classes may be grouped as; (I) where infiltration capacity of a soil is inadequate to deal with the amount of water supplied to the surface, because of topography, abnormal rainfall, or through inherent inability of the soil to transmit water internally, (II) where the groundwater table rises to a height detrimental to vegetative survival and/or soil structure, or where its presence hinders the function of a free draining subsoil, end (III) where a similar situation exists, due to a perched or elevated ground-water table. The allocation of a particular drainage problem to one or more of these broad classes is not usually difficult, but identification of causal processes within classes presents quite another problem. Often, drainage investigators have been content to evolve general treatments for each class, and, as a basic rule, such procedures have, more often than not, proved reasonably effective. However, with the increasing intensification of pastoral and agricultural farming, the fundamental causes of individual mal-drainage conditions must be positively identified and rectified within the broadly classified groups.
Keywords: Drainage; Soils -- Analysis